An overview on the dry heat treatment (DHT) for starch modification: Current progress and prospective applications - Hong-Ju He; Guanglei Li; Mohammed Obadi; Xingqi Ou (Current Research in Food Science)
Starch plays a pivotal role in numerous applications, making the enhancement of its functionality through physical processes increasingly important. Dry heat treatment (DHT) is a straightforward and eco-friendly technique that significantly improves starch characteristics and boosts food quality. This method has emerged as a focal point in starch modification research in recent years. This paper reviews current studies on the DHT of starches from various botanical sources, presenting key concepts and methodologies while delving into the impacts and mechanisms of DHT on the structural and physicochemical properties of starches. Furthermore, it elaborates on how additional components, such as ionic gums, amino acids, and sugars, can enhance the functionality of starches modified by DHT. Additionally, this review discusses the practical applications of dry heat-modified starches in the food industry, aiming to offer valuable insights for ongoing research and potential applications in enhancing food quality and functionality through innovative starch modifications.